Surat Dakwaan dalam Hukum Acara Pidana Sebagai Bentuk Mendukung Penegakan Hukum di Indonesia - S., Laurensius Arliman (Kosmik Hukum, 2019)
Abstract The indictment has a very important role in examining a criminal case in court by a judge, which is the basis for the judge in deciding a case and examine the case within the limits contained in the indictment. It is like that contained in Article 143 paragraph (1) Code of Criminal Procedure states prosecutor delegate a case to the District Court with a request to immediately try the case along with the indictment. In the Criminal Procedure knowledge there is no explanation of the purpose of this indictment. Keywords: Code of Criminal Procedure, Obstacles, Indictment Abstrak Surat dakwaan mempunyai peranan yang sangat penting dalam memeriksa suatu perkara pidana di persidangan oleh seorang hakim, dimana merupakan dasar bagi hakim dalam memutuskan suatu perkara dan memeriksa perkara dalam batasan-batasan yang termuat di dalam surat dakwaan. Sebagaimana dimuat di dalam Pasal 143 ayat (1) KUHAP, Penuntut Umum melimpahkan perkara ke Pengadilan Negeri dengan permintaan agar segera mengadili perkara tersebut disertai dengan surat dakwaan. Akan tetapi pengetahuan Hukum Acara Pidana tidak memberikan penjelasan mengenai maksud dari surat dakwaan tersebut. Kata kunci: Hukum Acara Pidana, Kendala, Surat Dakwaan